The Determinants and Performance Effects of Managers' Performance Evaluation Biases - Bol, Jasmijn C (The Accounting Review, 2011)
ABSTRACT This study examines the determinants and performance effects of centrality bias and leniency bias. The results show that managers respond to their own incentives and preferences when subjectively evaluating performance. Specifically, information-gathering costs and strong employee-manager relationships positively affect centrality bias and leniency bias. The findings also indicate that performance evaluation biases affect not only current performance ratings, but also future employee incentives. Inconsistent with predictions based on the agency perspective, the results show that managers' performance evaluation biases are not necessarily detrimental to compensation contracting. Although centrality bias negatively affects performance improvement, the evidence does not reveal a significant negative relation between leniency bias and performance. Rather, leniency bias is positively associated with future performance, which is consistent with the behavioral argument that bias can improve perceived fairness and, in turn, employee motivation. Data Availability: Data used in this study cannot be made public due to a confidentiality agreement with the participating firm.